Penyelidikan Perlapisan Bawah Permukaan Di Desa Labota, Kabupaten Morowali Menggunakan Resistivitas: Investigation of Subsurface Stratification in Labota Village, Morowali Regency, Using Resistivity - Al Rubaiyn; Usmardin; La Ode Sahiddin; Muhammad Ilham Kadar (Journal of Engineering Science and Technology Applications, 2026)
Labota Village in Morowali Regency holds significant potential for development in the areas of settlement, infrastructure, and natural resource exploration—specifically regarding groundwater and mineral deposits. To ensure the sustainable utilization of these resources, information regarding subsurface conditions is crucial. Combined geophysical survey results and field observations indicate that the uppermost layer in Labota Village consists of surface sediments or topsoil of relatively shallow thickness. Underlying this is a conglomerate rock layer with resistivity values ​​ranging from 2,000 Ωm to 20,000 Ωm. Quaternary sediments overlie ultramafic bedrock (Ku), which exhibits resistivity values ​​of ≥20,000 Ωm. The resistivity variations obtained from the survey are consistent with the lithological characteristics observed in the field, thereby reinforcing the interpretation of the subsurface layers